Droplet Tn-Seq combines microfluidics with Tn-Seq for identifying complex single-cell phenotypes - Derek Thibault (Nature Portfolio, 2019)
Culturing transposon-mutant libraries in pools can mask complex phenotypes. Here the authors present microfluidics mediated droplet Tn-Seq, which encapsulates individual mutants, promotes isolated growth and enables cell-cell interaction analyses.